Fluorescence in situ hybridisation (FISH) in histologically challenging conjunctival melanocytic lesions. Issue 1 (8th November 2012) - Mudhar, Hardeep Singh; Smith, Kath; Talley, Polly; Whitworth, Abigail; Atkey, Neil; Rennie, Ian G
Abstract : Background: Even in experienced hands, the classification of some melanocytic lesions of the conjunctiva remains challenging. In skin pathology, the recent application of fluorescence in situ hybridisation (FISH) has been demonstrated to be of use for the analysis and diagnosis of ambiguous melanocytic neoplasms of the skin. This study set out to evaluate this method on seven prospective conjunctival cases that were histologically equivocal. Methods: 18 unequivocal retrospective melanocytic controls were exposed to FISH. Commercially available probes assessing copy numbers of RREB1 (6p25), MYB (6q23) and CCND1 (11q13) genes compared with CEP6 (a chromosome six centromeric reference point) were used. After control verification, seven prospective, equivocal cases were identified and exposed to FISH. Results: There was complete correlation between FISH result and the control section histopathology report. Control cases of melanoma cases were all positive for FISH and control benign lesions were negative. Of the seven equivocal cases, five were positive and classed as invasive melanoma or melanoma-in situ, one was negative and one tetraploid, classed as negative (these last two cases were classed as naevi with careful clinical observation). Conclusions: FISH is very useful in classifying equivocal conjunctival melanocytic lesions, especially those with atypical junctional activity and naevoid melanocytic proliferations of the conjunctiva.